The impact of the means of communication on family relationships: Sociological field study in the city of Sulaymaniyah - Hussein, Twana Faraidun (Journal of University of Human Development, 2016)
This research tries to access to a range of outcomes, and to answer the fundamental question, a search (What is the impact of the means of communication on family relationships?).Try researcher through the form of a questionnaire to collect information in the field of the research community and in order to achieve his goal, And it relied on the questionnaire form for being an important means used extensively in sociology studies, The center of the city of Sulaymaniyah spatial boundaries of the search, where it is taken (200) and a sample search unit and distributed to three different areas (rich, middle and poor) by taking a stratified random sample, The fact that the population of the city of Sulaymaniyah different in terms of economic and cultural level, it’s easy to take the mixed researcher and different sample representing the research community in terms of level, category, and class. They were assembled for the purpose of research and study. It must be pointed out that this research is particularly important at the present time because the means of communication have spread widely in the Kurdish community and become accessible to everyone on the one hand, on the other hand, the number of users of these methods is increasing day by day, This is in addition to the increased demand for them constantly, making conduct such research in this importance area to see its impact on family relationships, and knowledge of its money from the effects (negative and positive) It is known that this means a double-edged her weapon of negative and positive effects at the same time, It must be the effort to reduce the negative effects of these tools and become members of the community in the service, and most importantly of all, do educate individuals on how to deal with these tools properly. It also offers search a set of proposals and recommendations to the concerned authorities to work out and strengthen the community in front of the challenges of the era of globalization of communications and response, where he became the Kurdish community a society open to the outside world through these means, which resulted in a change of values and social norms and behaviors that were adhered to by members of the community.